2013
DOI: 10.1002/pdi.1806
|View full text |Cite
|
Sign up to set email alerts
|

CSII experience among higher specialist trainees: a Young Diabetologists and Endocrinologists Forum survey

Abstract: Experience of the management of patients with type 1 diabetes treated with insulin pumps tends to vary significantly among clinicians in training. The Young Diabetologists and Endocrinologists Forum (YDEF), a body representing diabetes registrars, undertook a web‐based survey of doctors to assess their familiarity, confidence and experience in dealing with the various aspects of continuous subcutaneous insulin infusion (CSII) given its relative technical complexity and lack of formal training. A total of 101 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…4 Similarly, trainee doctors also reported little experience of training in insulin pumps. 5 There is currently no dedicated forum to support the ~160 UK insulin pump teams who are delivering insulin pump therapy and the associated emerging technologies. The authors hope that the IPN-UK will fill this gap, providing a platform for teams to communicate and work towards a shared vision of best practice.…”
Section: Role Of Abcd Ipn-ukmentioning
confidence: 99%
“…4 Similarly, trainee doctors also reported little experience of training in insulin pumps. 5 There is currently no dedicated forum to support the ~160 UK insulin pump teams who are delivering insulin pump therapy and the associated emerging technologies. The authors hope that the IPN-UK will fill this gap, providing a platform for teams to communicate and work towards a shared vision of best practice.…”
Section: Role Of Abcd Ipn-ukmentioning
confidence: 99%
“…The authors concluded that this may well be due to a lack of training of professional staff. 1,2 So with this in mind, the YDEF has continued to support and run the 3 day Insulin Pump Course. Behind the scenes, Dr Pratik Choudhary, Senior Lecturer and Consultant at King's College Hospital, put together a faculty of internationally recognised speakers and experienced members of the pump MDT, including senior DSNs and dieticians.…”
Section: Meeting Reportmentioning
confidence: 99%
“…The utilisation of CSII therapy in the UK is only 6%, lower than the anticipated 15–20% and lagging behind other European countries such as Germany, Norway (>15%) and America (>40%) 2,3. The recent United Kingdom Insulin Pump Audit confirmed a lack of trained health care professionals as a key factor limiting the expansion of CSII services within the UK and this has been further supported by a recent Young Diabetologists and Endocrinologists Forum survey 4,5…”
Section: Introductionmentioning
confidence: 99%